Factors Influencing Women's Perceptions of Shared Decision Making During Prenatal Care [13G]. (May 2020) - Vogel, Sarah; Breman, Rachel B.; Fahey, Jenifer; Crimmins, Sarah D.
Abstract : INTRODUCTION: Shared decision-making is central to providing patient-centered care and is associated with increased patient satisfaction, decreased healthcare costs and improved health outcomes. Women from different socio-economic, racial, and ethnic backgrounds may differ in their perceptions about the medical community and engagement in care. We sought to determine how patients perceived prenatal shared decision-making in an inner-city hospital serving a predominantly black population. METHODS: In an IRB-approved observational cross-sectional study at two different inner-city prenatal clinics, English-speaking women between 28 and 42 weeks' gestation completed a survey assessing shared decision-making. Maternal demographics and preferences towards prenatal education resources were collected. Our primary outcome was a participant's independence or dependence on a provider to make decisions about their care. Secondary outcomes included patient and provider perceptions of choices. Pearson Chi Square was used for analysis. RESULTS: Surveys were collected from 150 gravidas. Black women were more likely to be independent decision makers in their care in comparison to whites (25 [30.1%; of black women] vs 4 (8.9%; of white women [ P= .015]). No other factors demonstrated significance. Seven participants (4.6%) had not considered they had choices in their care. All of these participants were enrolled in government assistance programs ( P= .007). No differences were seen in the likelihood of providers discussing options for care with participants (P>.05 for all variables). CONCLUSION: Maternal race and socio-economic factors may significantly influence patients' perceptions of shared decision-making. Results from this research will help guide the development of an educational tool to provide adaptive discussions to improve the quality of patient-centered care.